2022
DOI: 10.1029/2021ja030147
|View full text |Cite
|
Sign up to set email alerts
|

The Drivers of the Martian Bow Shock Location: A Statistical Analysis of Mars Atmosphere and Volatile EvolutioN and Mars Express Observations

Abstract: The Martian interaction with the solar wind leads to the formation of a bow shock upstream of the planet. The shock dynamics appear complex, due to the combined influence of external and internal drivers. The extreme ultraviolet fluxes and magnetosonic Mach number are known major drivers of the shock location, while the influence of other possible drivers is less constrained or unknown such as crustal magnetic fields, solar wind dynamic pressure, or the Interplanetary Magnetic Field (IMF) intensity, and orient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 87 publications
(239 reference statements)
0
22
0
Order By: Relevance
“…However, the IMF intensity effect was not mentioned. Recently, Garnier et al (2022) found that the Martian terminator altitude, R TD , is apparently and positively correlated with the IMF intensity using the Mars Atmosphere and Volatile EvolutioN (MAVEN) and Mars Express (MEX) observations, which were also observed on Venus (Chai et al 2014). Theoretically, a stronger draping induced by an enhanced IMF can lead to the BS moving away from the planet (Bertucci et al 2011).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, the IMF intensity effect was not mentioned. Recently, Garnier et al (2022) found that the Martian terminator altitude, R TD , is apparently and positively correlated with the IMF intensity using the Mars Atmosphere and Volatile EvolutioN (MAVEN) and Mars Express (MEX) observations, which were also observed on Venus (Chai et al 2014). Theoretically, a stronger draping induced by an enhanced IMF can lead to the BS moving away from the planet (Bertucci et al 2011).…”
Section: Introductionmentioning
confidence: 96%
“…Besides the above factors, the influence of the IMF on the BS cannot be ignored (e.g., Vignes et al 2002;Garnier et al 2022). However, there were fewer studies involving the effect of IMF intensity on the location of the Martian BS, especially for the observations.…”
Section: Introductionmentioning
confidence: 99%
“…The changes might be partly due to the enhanced solar irradiance from the X8.2 flare. It should be mentioned that, the MAVEN orbit did not extend outside of the Martian BS during the surrounding orbits (5714, 5715, 5718, and 5719), mainly owing to the changes of the location and shape of the Martian BS caused by both external and internal drivers (Garnier et al 2022). The present study focuses on the observations upstream from the BS during orbits 5716 and 5717.…”
Section: Observation and Analysismentioning
confidence: 94%
“…(2000) for the MB location, for better agreement with ASPERA‐3 observations in the noon sector (Dubinin et al., 2006). It is worth noting that the average locations of these boundaries vary under the influence of different drivers (e.g., Garnier et al., 2002), including also the season and the solar cycle with slightly different parameters for the conics for the different Martian years covered by MAVEN (Simon Wedlund et al., 2022 and references therein).…”
Section: Observationsmentioning
confidence: 99%